Impact of apatinib in combination with osimertinib on EGFR T790M-positive lung adenocarcinoma - Liu, Yang; Xiong, Zhi-Cheng; Sun, Xin; Sun, Li; Zhang, Shu-Ling; Ma, Jie-Tao; Han, Cheng-Bo (Translational Cancer Research, 2019)
Background: The purpose of this study was to investigate the anti-tumor activities and the mechanisms of the third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) osimertinib, combined with the anti-angiogenic target drug apatinib, in the treatment of lung adenocarcinoma. We investigated the effects of these drugs in vitro in PC9 (E19 del) and H1975 (E21 L858R/E20 T790M) cell lines, as well as in vivo in both mouse and human experiments. Methods: PC9 and H1975 cells were cultured in 96-well plates and incubated with osimertinib (1–100 nmol/L), or apatinib (100–1,000 nmol/L), or a combination of the two agents, for 48 h. Cell viability was determined using a Cell Counting Kit-8. The protein expression of EGFR and its downstream signaling pathway members (AKT and ERK) was detected by western blot. For in vivo experiments, BALB/c nude mice were subcutaneously inoculated with H1975 cells in a xenograft model of adenocarcinoma. Mice bearing tumors were treated with osimertinib alone or in combination with apatinib, and tumor growth curves were obtained. Furthermore, we evaluated the efficacy and safety of combined osimertinib and apatinib therapy in three patients with EGFR T790M positive lung adenocarcinoma, who had been previously sensitized to osimertinib but developed an acquired resistance. Results: In vitro experiments revealed that osimertinib combined with apatinib increased the growth inhibition of PC9 and H1975 cells, simultaneously reducing the protein expression of phosphorylated EGFR and its downstream signaling pathway members in H1975 cells, compared to osimertinib treatment alone. In vivo experiments revealed that the combination of osimertinib and apatinib decreased tumor volume in an H1975 cell xenograft model, compared to osimertinib monotherapy at different dosages. All three patients with T790M positive lung adenocarcinoma that progressed following osimertinib treatment responded to continuous osimertinib in combination with apatinib, with a progression-free survival (PFS) range of 5–7 months. Conclusions: Apatinib can enhance the anti-tumor activity of osimertinib in the treatment of T790M positive lung adenocarcinoma. Further clinical studies are needed to confirm these results.